A produção de violência simbólica e a patologização como instrumento pedagógico - Barbi, Kathy Briones [UNESP] (2025)
Formal education plays a fundamental role in the development of children and adolescents within society. However, in recent times, there has been a persistent concern regarding school failure and the involvement of a “palette” of behaviors considered inappropriate for the educational environment, which intersect within this issue. This discussion, grounded in the school environment, has proven to be pertinent, and this dynamic has raised questions about the potential symbolic violence embedded in the process of referring students to educational psychology and institutional psychopedagogy services in response to behavioral and learning difficulties—most notably those related to reading and writing skills, which are expected by the end of the first cycle and in Portuguese language subjects in the second cycle. The objective of this research is to reflect on how the individualizing and pathological perspective of resolving and adapting to these deficits could be understood as a form of symbolic violence. Using a qualitative and theoretical-methodological approach, the study employed focus groups with teachers of 4th and 5th grades in elementary education (Cycle I) and Portuguese language teachers, as well as semi-structured interviews with institutional psychopedagogists and the Technical-Pedagogical Support Team responsible for the training of 4th and 5th-grade teachers and cycle recovery programs in the municipal education network of Araras-SP. Data analysis was conducted based on Pierre Bourdieu's theoretical framework, particularly the conceptual perspective of symbolic violence. The aim of these discussions and contributions is to understand how the basic education network in this municipality has been influenced by the pathologization of school failure.